Polypropylene composite material as well as preparation method and application thereof
By adding talc, elastomers, heat aging aids, and light aging aids to polypropylene resin, especially porous silica-loaded antioxidants and light stabilizers, the heat aging and light aging resistance of polypropylene composite materials are improved. This solves the problem of recycling waste bumpers and enables the efficient and stable application of automotive bumpers and other parts, resulting in significant economic and environmental benefits.
Patent Information
- Application Number
- CN202511625624.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-07
- Publication Date
- 2026-01-23
AI Technical Summary
In the existing technology, the application of recycled polypropylene material from waste bumpers in automobile bumper manufacturing is limited, making it difficult to meet the requirements for mechanical properties and weather resistance, resulting in a decline in the performance of the parts and an ineffective use of resources, causing environmental pollution and resource waste.
By adding talc, elastomer, heat aging aid, and light aging aid to polypropylene resin, especially by using porous silica-loaded antioxidants and light stabilizers, the heat aging and light aging resistance of the material can be improved, thus preparing a polypropylene composite material with excellent heat aging and light aging resistance.
This technology enables the efficient recycling of waste polypropylene materials from car bumpers, improves the performance of car bumpers and other parts, reduces production costs, and solves the problems of resource waste and environmental pollution, resulting in significant economic and environmental benefits.
Smart Images

Figure BDA0005676825620000091 
Figure BDA0005676825620000101 
Figure BDA0005676825620000111
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the technical field of high polymer materials, and particularly relates to a polypropylene composite material and a preparation method and application thereof. BACKGROUND
[0002] In the field of automobile manufacturing, as an important safety protection component, the selection and application of bumper materials have a profound impact on vehicle performance and environmental protection. Traditional bumper parts are mostly made of virgin polypropylene (PP) material. Although this material has good impact resistance, weather resistance and other properties, the production of virgin PP is highly dependent on petroleum resources, and consumes a large amount of energy and produces significant carbon emissions during production. On the other hand, with the continuous growth of the number of vehicles, a large amount of waste bumpers generated from the disassembly of waste vehicles has become a problem in solid waste treatment. If landfill treatment is used, polypropylene materials are difficult to degrade and will occupy land resources for a long time; incineration treatment will produce harmful gases such as dioxin, aggravate air pollution, and direct disposal may also lead to the spread of plastic pollution to soil and water, threatening the ecological system. In addition, if the polypropylene resources contained in waste bumpers are not effectively utilized, it will cause great waste of resources.
[0003] Currently, although some enterprises try to apply recycled plastics to the production of automobile parts, in the field of bumper parts, due to the strict requirements on the mechanical properties, weather resistance and other properties of the materials, the addition ratio of recycled materials and modification technology have always been a bottleneck. In the prior art, due to the unstable performance of recycled polypropylene materials, the aging resistance of the parts is reduced, which limits their large-scale application in the automobile industry.
[0004] Therefore, it is urgent to develop a technical solution that can effectively utilize waste bumper polypropylene materials and ensure the performance of the parts. SUMMARY
[0005] The present application aims to overcome the problems existing in the prior art and provide a polypropylene composite material and a preparation method and application thereof.
[0006] The present application is realized by the following technical solutions: In a first aspect, the present application provides a polypropylene composite material, which comprises the following components by weight: 22-84 parts of polypropylene resin, 4-11 parts of elastomer, 9-21 parts of talcum powder, 0.15-2.5 parts of thermal aging aid, and 0.18-1.2 parts of light aging aid. The thermal aging aid comprises an antioxidant, a neutralizing agent and porous silica A; the mass ratio of the antioxidant, the neutralizing agent and the porous silica A is (0.5-5):(0.5-3):1; The light aging aid includes a light stabilizer and porous silica B; and the mass ratio of the light stabilizer and the porous silica B is (0.5-3):1.
[0007] The polypropylene composite material of the present application has excellent heat aging resistance and light aging resistance, and can solve the problems of recycled polypropylene, realize the recycling of old polypropylene, and improve the heat aging resistance and light aging resistance of the composite material by loading antioxidants and light stabilizers on the porous silica and adding neutralizing agents to capture various free radicals generated in the application history.
[0008] In the polypropylene composite material of the present application, the weight fraction of the polypropylene resin is any one or a range value of two of 22 parts, 25 parts, 30 parts, 35 parts, 40 parts, 45 parts, 50 parts, 55 parts, 60 parts, 65 parts, 70 parts, 75 parts, 80 parts, 84 parts; the weight fraction of the elastomer is any one or a range value of two of 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts; the weight fraction of the talc is any one or a range value of two of 9 parts, 10 parts, 12 parts, 15 parts, 18 parts, 20 parts, 21 parts; the weight fraction of the heat aging aid is any one or a range value of two of 0.15 parts, 0.2 parts, 0.4 parts, 0.5 parts, 0.8 parts, 1 part, 1.2 parts, 1.5 parts, 2 parts, 2.5 parts; and the weight fraction of the light aging aid is any one or a range value of two of 0.18 parts, 0.2 parts, 0.4 parts, 0.6 parts, 0.8 parts, 1 part, 1.2 parts. The mass ratio of the antioxidant, the neutralizing agent and the porous silica A in the heat aging aid is any one or a range value of two of 0.5:0.5:1, 0.5:1:1, 0.5:2:1, 0.5:3:1, 2:0.5:1, 3:1:1, 3:2:1, 3:3:1, 4:1:1, 4:2:1, 4:3:1, 5:1:1, 5:3:1; and the mass ratio of the light stabilizer and the porous silica B in the light aging aid is any one or a range value of two of 0.5:1, 1:1, 1.5:1, 2:1, 2.5:1, 3:1.
[0009] Preferably, the polypropylene composite material comprises the following components by weight parts: polypropylene resin 25-80 parts, elastomer 5-10 parts, talcum powder 10-20 parts, heat aging aid 0.2-2 parts, light aging aid 0.2-1 part.
[0010] Preferably, the polypropylene resin comprises virgin polypropylene and recycled polypropylene, and the mass percentage of the recycled polypropylene in the polypropylene resin is not less than 30%; further, the mass percentage of the recycled polypropylene in the polypropylene resin is 40%-92%.
[0011] The recycled polypropylene can be used in the polypropylene resin of the present application, thereby solving the problem of recycling of old polypropylene.
[0012] Specifically, the preparation method of the heat aging aid can be: dissolving the antioxidant in a solvent (such as toluene), then mixing with porous silica A, stirring uniformly, then standing, allowing the solution to penetrate into the pores of the porous silica A by capillary force, drying, then mixing with a neutralizing agent to obtain the heat aging aid; the preparation method of the light aging aid can be: dissolving the light stabilizer in a solvent (such as toluene), then mixing with porous silica B, stirring uniformly, then standing, allowing the solution to penetrate into the pores of the porous silica B by capillary force, drying to obtain the light aging aid.
[0013] Preferably, the average particle size of the porous silica A and the porous silica B is independently 10 nm-5 μm.
[0014] Preferably, the pore size of the porous silica A and the porous silica B is independently 2 nm-50 nm; the pore size of the porous silica A and the porous silica B of the present application is in the mesoporous range.
[0015] Preferably, the specific surface area of the porous silica A and the porous silica B is independently 50 m2 / g-600 m 2 / g.
[0016] Specifically, the test method of the specific surface area is the multipoint adsorption method, and the test standard is GB / T 19587-2017; the test method of the average particle size of the porous silica is the laser diffraction method, and the test standard is ISO 13320:2020.
[0017] Preferably, the porous silica comprises large particle size particles, medium particle size particles and small particle size particles; the average particle size a of the large particle size particles is 2.5 μm≤a≤3.5 μm, the average particle size b of the medium particle size particles is 1 μm≤b≤2 μm, and the average particle size c of the small particle size particles is 10 nm≤c≤40 nm; the mass ratio of the large particle size particles, the medium particle size particles and the small particle size particles is (1-2):(1-2):1.
[0018] The porous silica of the present application preferably adopts a compound of particles with different particle sizes, which can form a gradient composite structure with particle sizes from large to small. During the mixing process, large-particle-size carriers are preferentially distributed in the outer layer of the composite material, and small-particle-size carriers penetrate into the inner layer, achieving gradient protection of ultraviolet rays and thermal oxidation from the outside to the inside, and improving the overall protection effect.
[0019] Preferably, the antioxidant includes at least one of hindered phenolic antioxidants and phosphite antioxidants.
[0020] Preferably, the neutralizing agent includes at least one of hydrotalcite, magnesium oxide, and aluminum oxide, and has a particle size ranging from 0.1 nm to 50 pm.
[0021] Polypropylene will generate -OH / -C=O groups and other groups when aging, making the entire system acidic. The addition of the neutralizing agent in the present application can neutralize these acidic groups, making the entire system neutral.
[0022] Preferably, the light stabilizer is a hindered amine light stabilizer.
[0023] Optionally, the hydrotalcite has an average particle size of 4 nm to 10 pm; the antioxidant has an average particle size of 1 nm to 50 pm; and the light stabilizer has an average particle size of 1 nm to 10 pm.
[0024] Specifically, the average particle size of the neutralizing agent, antioxidant, and light stabilizer is tested by laser diffraction method, and the test standard is ISO 13320:2020.
[0025] Preferably, the recycled polypropylene has a melt flow rate of 10-20 g / 10 min at 230°C and under a 2.16 kg weight according to ISO1133-2012.
[0026] Optionally, the recycled polypropylene of the present application is derived from a waste bumper paint removal sheet.
[0027] Preferably, the virgin polypropylene has a melt flow rate of 10-50 g / 10 min at 230°C and under a 2.16 kg weight according to ISO1133-2012.
[0028] Specifically, the virgin polypropylene is a copolymerized polypropylene.
[0029] Preferably, the elastomer is a polyolefin elastomer.
[0030] Preferably, the polyolefin elastomer has a melt flow rate of 0.5-10 g / 10 min at 190°C and under a 2.16 kg weight according to ISO1133-2012.
[0031] Optionally, the polyolefin elastomer is an ethylene-butene copolymer.
[0032] Preferably, the mass percentage of the polypropylene resin in the polypropylene composite material is not less than 60%.
[0033] Preferably, the melt flow rate of the polypropylene composite material according to ISO1133-2012 at 230 DEG C, 2.16 kg weight is 20-35 g / 10 min.
[0034] In a second aspect, the present application provides a preparation method of the polypropylene composite material, comprising the following steps: uniformly mixing the components according to the weight fractions, melt extruding through a double screw extruder, granulating, and obtaining the polypropylene composite material.
[0035] The preparation method of the present application is simple and can realize industrial scale production.
[0036] Preferably, the melt extruding conditions are as follows: zone 1 temperature 75-85 DEG C, zone 2 temperature 185-195 DEG C, zone 3 temperature 185-195 DEG C, zone 4 temperature 185-195 DEG C, zone 5 temperature 185-195 DEG C, zone 6 temperature 185-195 DEG C, zone 7 temperature 185-195 DEG C, zone 8 temperature 185-195 DEG C, zone 9 temperature 185-195 DEG C; main machine rotation speed 400-500 rpm; length-diameter ratio of the double screw extruder (44-48):1.
[0037] In a third aspect, the present application provides an application of the polypropylene composite material or the polypropylene composite material prepared by the preparation method of the polypropylene composite material in automobile parts.
[0038] The polypropylene composite material of the present application has high fluidity, rigidity and toughness, and simultaneously has excellent heat aging resistance and light aging resistance, and can be used in automobile parts such as bumpers, grilles, side beams, etc.
[0039] In a fourth aspect, the present application provides a vehicle-mounted part, which is prepared using the polypropylene composite material or the polypropylene composite material prepared by the preparation method of the polypropylene composite material.
[0040] Optionally, the vehicle-mounted part is one of a bumper, a grille and a side beam.
[0041] The application has the following beneficial effects: the application adds a specific content of recycled polypropylene, talcum powder, elastomer, heat aging aid and light aging aid in new material polypropylene, and obtains polypropylene composite material with excellent heat aging resistance and light aging resistance, thereby reducing the production cost, realizing the performance standard of bumper parts, filling the technical gap of efficient and stable application of waste bumper polypropylene material in automobile bumper parts, and having remarkable economic value and environmental protection benefit. DETAILED DESCRIPTION
[0042] In order to better illustrate the purpose, technical scheme and advantages of the present application, the present application will be further described below in combination with specific examples. Those skilled in the art should understand that the specific examples described herein are only used to explain the present application and do not limit the present application.
[0043] Unless otherwise specified, the test methods used in the examples are conventional methods; and the materials, reagents, etc. used, unless otherwise specified, can be obtained from commercial channels.
[0044] Examples 1-14 The composition of the polypropylene composite material described in the examples of the present application is shown in Table 1.
[0045] The preparation method of the polypropylene composite material comprises the following steps: uniformly mixing the components according to the weight fractions, melt extruding through a double screw extruder, granulating and drying, and obtaining the product; the melt extrusion conditions are as follows: the temperature of the first zone is 80℃, the temperature of the second zone is 190℃, the temperature of the third zone is 190℃, the temperature of the fourth zone is 190℃, the temperature of the fifth zone is 190℃, the temperature of the sixth zone is 190℃, the temperature of the seventh zone is 190℃, the temperature of the eighth zone is 190℃, the temperature of the ninth zone is 190℃, and the main machine rotation speed is 450 revolutions / minute; the length-diameter ratio of the double screw extruder is 48:1.
[0046] Comparative Examples 1-8 The difference between the comparative examples 1-8 and the examples is only in the types and proportions of the components, as shown in Table 2.
[0047] In the components described in each example and comparative example, The recycled polypropylene is a waste bumper paint-removed sheet material, RPP DCT-2045PB21 (MK) of Langfang Maiko Plastic Technology Co., Ltd., the main components of which are copolymerized polypropylene, ethylene-octene copolymer, talcum powder and color masterbatch. The waste bumper is crushed into a sheet material, the sheet material is placed in sand to polish and remove the surface paint layer, and after the processes of cleaning, filtering and drying, a clean paint-removed bumper sheet material is obtained, which is the recycled polypropylene, and the melt flow rate thereof under 230℃ and 2.16kg weight according to ISO1133-2012 is 15g / 10min. The virgin polypropylene-1 is: PP EP548RQ, Sinopec, the melt flow rate is 28 g / 10 min under 230℃, 2.16 kg weight according to ISO1133-2012; The virgin polypropylene-2 is: PP EP300M, Sinopec, the melt flow rate is 10 g / 10 min under 230℃, 2.16 kg weight according to ISO1133-2012; The virgin polypropylene-3 is: PP EP5075X, Sinopec, the melt flow rate is 50 g / 10 min under 230℃, 2.16 kg weight according to ISO1133-2012; The elastomer is ethylene-butene copolymer: POE Engage 7467, Dow Chemical, the melt flow rate is 0.8 g / 10 min under 190℃, 2.16 kg weight according to ISO1133-2012; The talc is: TYT-777A, Guangzhou Tianyuan; The thermal aging aid-1 includes antioxidant, neutralizing agent and porous silica A; the mass ratio of the antioxidant, neutralizing agent and porous silica A is 3:2:1; the porous silica A includes large particle size particles, medium particle size particles and small particle size particles; the average particle size of the large particle size particles is 3.2 μm, the average particle size of the medium particle size particles is 1.5 μm, and the average particle size of the small particle size particles is 40 nm; the mass ratio of the large particle size particles, medium particle size particles and small particle size particles is 1:1:1; the thermal aging aid-2 includes antioxidant, neutralizing agent and porous silica A; the mass ratio of the antioxidant, neutralizing agent and porous silica A is 0.5:0.5:1; the porous silica A includes large particle size particles, medium particle size particles and small particle size particles; the average particle size of the large particle size particles is 3.2 μm, the average particle size of the medium particle size particles is 1.5 μm, and the average particle size of the small particle size particles is 40 nm; the mass ratio of the large particle size particles, medium particle size particles and small particle size particles is 1:1:1; The thermal aging aid-3 comprises an antioxidant, a neutralizing agent and porous silica A; the mass ratio of the antioxidant, the neutralizing agent and the porous silica A is 5:3:1; the porous silica A comprises large particle size particles, medium particle size particles and small particle size particles; the average particle size of the large particle size particles is 3.2 μm, the average particle size of the medium particle size particles is 1.5 μm, and the average particle size of the small particle size particles is 40 nm; the mass ratio of the large particle size particles, the medium particle size particles and the small particle size particles is 1:1:1; the thermal aging aid-4 comprises an antioxidant, a neutralizing agent and porous silica A; the mass ratio of the antioxidant, the neutralizing agent and the porous silica A is 3:2:1; the porous silica A comprises large particle size particles, medium particle size particles and small particle size particles; the average particle size of the large particle size particles is 3.2 μm, the average particle size of the medium particle size particles is 1.5 μm, and the average particle size of the small particle size particles is 40 nm; the mass ratio of the large particle size particles, the medium particle size particles and the small particle size particles is 2:2:1; the thermal aging aid-5 comprises an antioxidant, a neutralizing agent and porous silica A; the mass ratio of the antioxidant, the neutralizing agent and the porous silica A is 3:2:1; the porous silica A is a medium particle size particle, and the average particle size of the medium particle size particle is 1.5 μm; The thermal aging aid-6 comprises an antioxidant, a neutralizing agent and porous silica A; the mass ratio of the antioxidant, the neutralizing agent and the porous silica A is 3:2:1; the porous silica A comprises large particle size particles, medium particle size particles and small particle size particles; the average particle size of the large particle size particles is 3.2 μm, the average particle size of the medium particle size particles is 1.5 μm, and the average particle size of the small particle size particles is 40 nm; the mass ratio of the large particle size particles, the medium particle size particles and the small particle size particles is 1:1.5:1; the thermal aging aid-7 comprises an antioxidant and a neutralizing agent; the mass ratio of the antioxidant and the neutralizing agent is 3:2; The thermal aging aid-8 comprises an antioxidant, a neutralizing agent and porous silica A; the mass ratio of the antioxidant, the neutralizing agent and the porous silica A is 0.2:0.2:1; the porous silica A comprises large particle size particles, medium particle size particles and small particle size particles; the average particle size of the large particle size particles is 3.2 μm, the average particle size of the medium particle size particles is 1.5 μm, and the average particle size of the small particle size particles is 40 nm; the mass ratio of the large particle size particles, the medium particle size particles and the small particle size particles is 1:1:1; The thermal aging aid-9 includes an antioxidant, a neutralizing agent and porous silica A; the mass ratio of the antioxidant, the neutralizing agent and the porous silica A is 6:4:1; the porous silica A includes large particle size particles, medium particle size particles and small particle size particles; the average particle size of the large particle size particles is 3.2 μm, the average particle size of the medium particle size particles is 1.5 μm, and the average particle size of the small particle size particles is 40 nm; the mass ratio of the large particle size particles, the medium particle size particles and the small particle size particles is 1:1:1; the preparation method of the above thermal aging aid is: using toluene to dissolve the antioxidant, then mixing with the porous silica, stirring uniformly, standing, letting the solution penetrate into the pore channel of the porous silica by capillary force, drying, and then mixing with the neutralizing agent to obtain the thermal aging aid; The light aging aid-1 includes a light stabilizer and porous silica B; the mass ratio of the light stabilizer and the porous silica B is 2:1; the porous silica B includes large particle size particles, medium particle size particles and small particle size particles; the average particle size of the large particle size particles is 3.2 μm, the average particle size of the medium particle size particles is 1.5 μm, and the average particle size of the small particle size particles is 40 nm; the mass ratio of the large particle size particles, the medium particle size particles and the small particle size particles is 1:1:1; The light aging aid-2 includes a light stabilizer and porous silica B; the mass ratio of the light stabilizer and the porous silica B is 0.5:1; the porous silica B includes large particle size particles, medium particle size particles and small particle size particles; the porous silica B includes large particle size particles, medium particle size particles and small particle size particles; the average particle size of the large particle size particles is 3.2 μm, the average particle size of the medium particle size particles is 1.5 μm, and the average particle size of the small particle size particles is 40 nm; the mass ratio of the large particle size particles, the medium particle size particles and the small particle size particles is 1:1:1; The light aging aid-3 includes a light stabilizer and porous silica B; the mass ratio of the light stabilizer and the porous silica B is 3:1; the porous silica B includes large particle size particles, medium particle size particles and small particle size particles; the average particle size of the large particle size particles is 3.2 μm, the average particle size of the medium particle size particles is 1.5 μm, and the average particle size of the small particle size particles is 40 nm; the mass ratio of the large particle size particles, the medium particle size particles and the small particle size particles is 2:1:1; The light aging aid-4 includes a light stabilizer and porous silica B; the mass ratio of the light stabilizer and the porous silica B is 2:1; the porous silica B includes large particle size particles, medium particle size particles and small particle size particles; the average particle size of the large particle size particles is 3.2 μm, the average particle size of the medium particle size particles is 1.5 μm, and the average particle size of the small particle size particles is 40 nm; the mass ratio of the large particle size particles, the medium particle size particles and the small particle size particles is 2:2:1; The photoaging aid-5 comprises a light stabilizer and porous silica B; the mass ratio of the light stabilizer and porous silica B is 2:1; the porous silica B is a medium particle size particle, and the average particle size of the medium particle size particle is 1.5 μm; the photoaging aid-6 comprises a light stabilizer and porous silica B; the mass ratio of the light stabilizer and porous silica B is 2:1; the porous silica B comprises large particle size particles, medium particle size particles and small particle size particles; the average particle size of the large particle size particles is 3.2 μm, the average particle size of the medium particle size particles is 1.5 μm, and the average particle size of the small particle size particles is 40 nm; the mass ratio of the large particle size particles, the medium particle size particles and the small particle size particles is 1:1.5:1; The photoaging aid-7 is a light stabilizer; The photoaging aid-8 comprises a light stabilizer and porous silica B; the mass ratio of the light stabilizer and porous silica B is 0.2:1; the porous silica B comprises large particle size particles, medium particle size particles and small particle size particles; the average particle size of the large particle size particles is 3.2 μm, the average particle size of the medium particle size particles is 1.5 μm, and the average particle size of the small particle size particles is 40 nm; the mass ratio of the large particle size particles, the medium particle size particles and the small particle size particles is 1:1:1; The photoaging aid-9 comprises a light stabilizer and porous silica B; the mass ratio of the light stabilizer and porous silica B is 4:1; the porous silica comprises large particle size particles, medium particle size particles and small particle size particles; the average particle size of the large particle size particles is 3.2 μm, the average particle size of the medium particle size particles is 1.5 μm, and the average particle size of the small particle size particles is 40 nm; the mass ratio of the large particle size particles, the medium particle size particles and the small particle size particles is 1:1:1; The large particle size particles in the above-mentioned porous silica A and porous silica B are: S200, Cabot, the average particle size is 3.2 μm according to the test standard of ISO 13320:2020; The medium particle size particles are: K45, Lingwei Technology, the average particle size is 1.5 μm according to the test standard of ISO 13320:2020; The small particle size particles are: OX50, Evonik, the average particle size is 40 nm according to the test standard of ISO 13320:2020; The antioxidant is: hindered phenolic antioxidant, CAS number: 40601-76-1, BASF Chemical; The neutralizing agent is: hydrotalcite, DHT-4A, Benxi Union Chemical; The light stabilizer is a hindered amine light stabilizer, CAS No. 167078-06-0, Japan Adico; The preparation method of the above light aging aid is: dissolving the light stabilizer with toluene, then mixing with porous silica, stirring uniformly, standing, allowing the solution to penetrate into the pore channel of the porous silica by capillary force, drying, to obtain the light aging aid. The component raw materials used in each embodiment and comparative example of the present application are commercially available raw materials unless otherwise specified, and the component raw materials used in each parallel experiment are the same.
[0048] Table 1 Component content (parts) in materials of examples 1-14 Table 2 Component content (parts) in materials of comparative examples 1-8 In order to verify the performance of the polypropylene composite material described in the present application, the products prepared in each example and comparative example are subjected to the following performance tests, as follows: (1) Flexural modulus: using ISO 178 test standard, the material is under the condition of 23℃, 2mm / min, 64mm span, the flexural modulus is ≥1400MPa; (2) Impact performance: using ISO 179-1 / 1Ea test standard, the material is under the condition of 23℃, the notched Charpy impact performance is ≥30kJ / m 2 ; (3) Heat aging performance: the sample plate is stored in a constant temperature ventilated oven at 150℃, and the time when the sample plate shows typical heat aging phenomena such as differentiation, pulverization, cracking or embrittlement is recorded; (4) Light aging performance: using the test standard of Volkswagen PV3929, the sample plate is required to have a gray scale of ≥4 after 1500h light aging.
[0049] The test results are shown in Tables 3 and 4.
[0050] Table 3 Performance test results of materials of examples 1-14 Table 4 Performance test results of materials of comparative examples 1-8 From Tables 3 and 4, it can be seen that the polypropylene composite material of the present application has excellent mechanical properties, light aging and heat aging performance, the flexural modulus is >1400MPa, the notched Charpy impact performance is ≥33kJ / m 2 , the heat aging time at 150℃ is >290h, and the light aging gray scale after 1500h is ≥4.
[0051] Melt flow rate tests were conducted on the polypropylene composite materials of the examples. The polypropylene composite materials of Examples 1 to 14 showed high fluidity with melt flow rates of 21-28 g / 10 min at 230 °C and 2.16 kg weight, according to ISO 1133-2012. In contrast, the polypropylene composite materials obtained in Comparative Examples 1 to 8 had melt flow rates of no more than 21 g / 10 min, and their fluidity was weaker than that of the examples.
[0052] Furthermore, the absence of a heat aging aid in Comparative Example 1 resulted in a significant decrease in the material's heat aging performance. The lack of a photoaging aid in Comparative Example 2 led to a significant reduction in the material's photoaging performance. The absence of porous silica in the heat aging aid in Comparative Example 3 resulted in the antioxidant not being evenly dispersed in the matrix resin, causing preferential aging in areas with less dispersed heat aging aid, thus generating a large number of free radicals and accelerating material aging. The poor ratio of antioxidant, neutralizer, and porous silica in the heat aging aids of Comparative Examples 4 and 5 resulted in poor synergistic effects between components, leading to a decrease in the overall performance of the material. The lack of porous silica in the photoaging aid of Comparative Example 6 resulted in poor dispersion of the light stabilizer in the matrix resin, leading to a significant decrease in the material's photoaging performance. The poor mass ratio of light stabilizer to porous silica in Comparative Examples 7 and 8 resulted in reduced resistance to photothermal aging.
[0053] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.
Claims
1. A polypropylene composite, characterized in that, The polypropylene composite material comprises the following components by weight parts: polypropylene resin 22-84 parts, elastomer 4-11 parts, talcum powder 9-21 parts, heat aging aid 0.15-2.5 parts, light aging aid 0.18-1.2 parts; The heat aging aid comprises an antioxidant, a neutralizing agent and porous silica A; the mass ratio of the antioxidant, the neutralizing agent and the porous silica A is (0.5-5):(0.5-3):1; The light aging aid comprises a light stabilizer and porous silica B; the mass ratio of the light stabilizer and the porous silica B is (0.5-3):
1.
2. The polypropylene composite of claim 1, wherein, The average particle size of the porous silica A and the porous silica B is independently 1 μm-100 μm.
3. The polypropylene composite of claim 1, wherein, The porous silica A and the porous silica B independently comprise large particle size particles, medium particle size particles and small particle size particles; the average particle size a of the large particle size particles is 20 μm≤a≤100 μm, the average particle size b of the medium particle size particles is 10 μm≤b≤20 μm, and the average particle size c of the small particle size particles is 1 μm≤c≤10 μm; the mass ratio of the large particle size particles, the medium particle size particles and the small particle size particles is (1-2):(1-2):
1.
4. The polypropylene composite of claim 1, wherein, The antioxidant comprises at least one of hindered phenolic antioxidants and phosphite antioxidants; and / or the neutralizing agent comprises at least one of hydrotalcite, magnesium oxide and aluminum oxide; and / or the light stabilizer is a hindered amine light stabilizer.
5. The polypropylene composite of claim 1, wherein, The polypropylene resin comprises virgin polypropylene and recycled polypropylene, and the mass percentage of the recycled polypropylene in the polypropylene resin is not less than 30%.
6. The polypropylene composite of claim 5, wherein, The melt flow rate of the virgin polypropylene at 230℃ under a 2.16 kg weight according to ISO1133-2012 is 10-50 g / 10 min; and / or the melt flow rate of the recycled polypropylene at 230℃ under a 2.16 kg weight according to ISO1133-2012 is 10-20 g / 10 min.
7. The polypropylene composite of claim 1, wherein, The elastomer is a polyolefin elastomer.
8. A process for the production of a polypropylene composite material according to any one of claims 1 to 7, characterized in that, The method comprises the following steps: The components are mixed uniformly by weight parts, melt-extruded through a double-screw extruder, granulated, and the polypropylene composite material is obtained.
9. The polypropylene composite material of any one of claims 1-7 or the polypropylene composite material prepared by the method of claim 8 is used in an automobile part.
10. A vehicle interior component, characterized by The automobile part is prepared using the polypropylene composite material of any one of claims 1-7 or the polypropylene composite material prepared by the method of claim 8.
